Representations of *-algebras, locally compact groups, and Banach *-algebraic bundles - Fell, J. M. G. (Pure and applied mathematics, 1988)
v. 1. Basic representation theory of groups and algebras -- v. 2. Banach *-algebraic bundles, induced representations, and the generalized Mackey analysis